A plot-based elevational assessment of species densities, life forms and leaf traits of seed plants in the south-eastern Himalayan biodiversity hotspot, North Myanmar. (1st November 2020) - Nowak, Pauline; Khine, Phyo Kay; Homeier, Jürgen; Leuschner, Christoph; Miehe, Georg; Kluge, Jürgen
ABSTRACT: Background : Species density along elevation gradients often shows hump-shaped patterns, but in-depth data for Myanmar is still not available. Aim : The first plot-based study to detect the elevational patterns of life forms and tree leaf traits, and their relation to environmental factors in Myanmar. Methods : All seed plant species were recorded on 76 plots between 400 and 4100 m. Regression models were used to identify the variables with highest predictive power for species densities of different life forms and leaf traits. Results : Species density showed a linear elevational decline except for grasses (increase) and epiphytes (hump-shaped pattern) and were related to temperature and precipitation in all considered life forms. Tree leaf size, the proportion of species with simple leaves and leaves with drip tips decreased with elevation, while the proportion of toothed leaves increased. Conclusions : Our data partly confirm some widely held assumptions about elevation patterns in species density and leaf traits. While the climatic dependence behaves as expected, leaf traits and lifeforms show mixed and sometimes surprising patterns. Previous knowledge of these patterns is partly confirming, but highly scattered regionally, so our study performed in one region offers a rare opportunity towards a natural history image of a biodiversity hotspot..